Does population sorting through internal migration increase healthcare costs and needs in peripheral regions? - Shobhit Kulshreshtha; Martin Salm; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Large regional disparities in health and healthcare costs prevail in many countries, but our understanding of the underlying causes is still limited. This study shows for the case of the Netherlands that population sorting through internal migration can explain a substantial share, around 28%, of regional variation in healthcare costs. Internal migration during the 1998-2018 period increases average healthcare costs in peripheral provinces by up to 3%. Most of this effect can be attributed to selective migration. We find similar results for risk scores, a measure of healthcare needs. The Dutch risk equalization scheme compensates only partially for these effects. – – In vielen Ländern gibt es große regionale Unterschiede bei der Gesundheit und den Gesundheitskosten, aber unser Verständnis der zugrunde liegenden Ursachen ist immer noch begrenzt. In dieser Studie wird für die Niederlande gezeigt, dass die Bevölkerungszusammensetzung durch Binnenmigration einen erheblichen Anteil, etwa 28 %, der regionalen Unterschiede bei den Gesundheitskosten erklären kann. Die Binnenmigration im Zeitraum 1998-2018 erhöht die durchschnittlichen Gesundheitskosten in peripheren Provinzen um bis zu 3 %. Der größte Teil dieses Effekts kann auf selektive Migration zurückgeführt werden. Wir finden ähnliche Ergebnisse für Risikoscores, ein Maß für Gesundheitsbedürfnisse. Der niederländische Risikoausgleich gleicht diese Effekte nur teilweise aus.
Keywords: H51; I14; R23; 330; Regional variation in healthcare costs; internal migration; movers approach; regionaldisparities